Second Language Learners’ Perceptions of Conversations in English Materials - Yu Hui; Thora Tenbrink (SAGE Open)
This study addresses how Chinese learners of English as a second language (L2) perceive conversations in English materials as compared to speakers of English as a first language (L1). Data were collected through questionnaires completed by 48 participants (28 L2 English learners in China and 20 L1 English speakers in the UK), eliciting evaluations of written versions of two conversations from the International English Language Testing System (IELTS) and the College English Test (CET) Band 6 of China. Overall, learners favored the CET conversation, but L1 speakers preferred the IELTS one. A content analysis uncovered five major attention foci among participants: Language, Discourse, Content, Context, and Learning, with L1 speakers focusing more on the genuineness of language at a macro level than learners, who mostly attended to words and sentence structure. More detailed discourse analysis of lexical items reflecting appraisal highlighted that learners showed high awareness of context-related authenticity and evaluated difficulty with respect to a wide range of aspects, whereas L1 speakers evaluated the authenticity at language and discourse levels and commented on the perceived difficulty of content and learning. Implications for teaching and learning spoken English with materials include the importance of offering explicit information about authenticity and spoken features of conversations that students may otherwise fail to notice.